Blood and organ donation: health impact, prevalence, correlates, and interventions. Issue 9 (2nd September 2019) - Ferguson, Eamonn; Murray, Catherine; O'Carroll, Ronan E.
Abstract: Objective: Without a supply of blood, health services could not meet their clinical needs. Similarly, organs for transplantation save and transform lives. Donations are acts of generosity that are traditionally seen as altruistic, and accordingly, interventions to recruit and retain blood and organ donors have focused on altruism. We review the predictors, prevalence and correlates of these two behaviours, how effective interventions have been, and draw common themes. Design: Narrative review. Results: We highlight that both recipients and donors benefit, and as such neither blood nor organ donation is purely altruistic. We also highlight health problems associated with both types of donation. In evaluating interventions, we highlight that a move to an opt-out policy for organ donation may not be the simple fix it is believed to be, and propose interventions to enhance the effectiveness of an opt-in policy (e.g. social media updates). We show that incentives, text messaging, feedback and a focus on prosocial emotions (e.g. 'warm-glow', 'gratitude') may be effective interventions for both blood and organ donation. Interventions designed to reduce fainting (e.g. water pre-loading) are also effective for blood donation. Conclusions : We conclude that affect is key to understanding both types of donation and in designing effective interventions.